CHILD SUPPORT AWARDS AND COMPLIANCE ENFORCEMENT IN ENGLISH FAMILY LAW (World Bulletin of Management and Law, 2023)
In this article the principal notions used in international law. Under the international private law the main areas of activity of legal systems of various legal orders are identified. The focus of the study is issues related to marriage and divorce. Europe and Asia have different approaches to the regulation of marriage and family relations. Asian countries base on the religious frame, which largely dictate their legal status. Priority is given to customs and traditions that have been shaped over the centuries. Europe is more flexible and inclined to reforms. The use of binding formulas facilitates consensus between states regarding the application of a particular legal norm. The purpose of the study is the correlation and analysis of national laws regulating marriage and divorce in international private law
Keywords: English family law; Conflict of Laws Norms; Marriage And Family Relations